KELIMPAHAN DAN KEANEKARAGAMAN JENIS-JENIS KEPITING DI SUBSTRAT MANGROVE PERAIRAN MERAS DAN MOLAS KECAMATAN BUNAKEN KOTA MANADO SULAWESI UTARA - Rivaldo A Wuisan; Erly Kaligis (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Crab of the genus Uca is one type of crustacean that makes mangroves a habitat to carry out their life cycle in order to remain sustainable. The purpose of this research is to identify the first, the second is to calculate the abundance, species diversity, dominance, and the third is to know the state of the aquatic environment around pH, temperature, salinity and substrate. The method used is the cruising method and the quadratic line transect method. The method of roaming as far as 300 m. While the line transect method is carried out by drawing three transect lines along 28 m. The identification results in Meras waters found 6 species. Based on data analysis using the cruising method, the number of individuals in Meras waters is 383 individuals, while in Molas waters there are 210 individuals. Based on data analysis using the quadratic line transect method, the species abundance index in Meras waters is 6,767 ind/m2, while in Molas waters it is 4,533 ind/m2. The value of H' at two locations is moderate. The value of C in two locations is low. Keywords: Meras, Molas, Crabs, abundance, species diversity, dominance.